Effects of the Digital Game-Based Learning (DGBL) on Students Academic Performance in Arabic Learning at Sambas Purbalingga - Aziz, Annas Nur; Subiyanto, Subiyanto; Harlanu, Muhammad (KARSA Journal of Social and Islamic Culture, 2018)
Arabic has been an official language of the United Nations since 1971. However, infrastructure, availability of technology by either students or teachers and professional training for teacher’s technological usage in Arabic teaching are still lacking. This paper presents the effectiveness of Digital Game-Based Learning as media towards studentsâ€™ academic performance in Arabic learning. DGBL was designed by ADDIE model. Quasi experimental Design was used as the method for the implementation phase. The sample of this study was 72 students of the first grade of junior high school. They were divided into two groups of 36 respectively: Group A as the experimental group and Group B as the control group. Group A was treated with DGBL method whereas Group B treated with The Non-DGBL method. The learning results showed that Group A performed significantly higher than Group B cause the results of t table is smaller than the result based on t-Test value (1,67 < 3,244). The Digital Game-Based Learning (DGBL) suggested being used as a tool to increase studentâ€™s academic performance in Arabic learning for high school students.